Altered synaptic protein expression, aberrant spine morphology, and impaired spatial memory in Dlgap2 mutant mice, a genetic model of autism spectrum disorder. (28th September 2022) - Hsieh, Ming-Yen; Tuan, Li-Heng; Chang, Ho-Ching; Wang, Yu-Chun; Chen, Chia-Hsiang; Shy, Horng-Tzer; Lee, Li-Jen; Gau, Susan Shur-Fen
Abstract: A microdeletion of approximately 2.4 Mb at the 8p23 terminal region has been identified in a Taiwanese autistic boy. Among the products transcribed/translated from genes mapped in this region, the reduction of DLGAP2, a postsynaptic scaffold protein, might be involved in the pathogenesis of autism spectrum disorder (ASD). DLGAP2 protein was detected in the hippocampus yet abolished in homozygous Dlgap2 knockout ( Dlgap2 KO) mice. In this study, we characterized the hippocampal phenotypes in Dlgap2 mutant mice. Dlgap2 KO mice exhibited impaired spatial memory, indicating poor hippocampal function in the absence of DLGAP2. Aberrant expressions of postsynaptic proteins, including PSD95, SHANK3, HOMER1, GluN2A, GluR2, mGluR1, mGluR5, βCAMKII, ERK1/2, ARC, BDNF, were noticed in Dlgap2 mutant mice. Further, the spine density was increased in Dlgap2 KO mice, while the ratio of mushroom-type spines was decreased. We also observed a thinner postsynaptic density thickness in Dlgap2 KO mice at the ultrastructural level. These structural changes found in the hippocampus of Dlgap2 KO mice might be linked to impaired hippocampus-related cognitive functions such as spatial memory. Mice with Dlgap2 deficiency, showing signs of intellectual disability, a common co-occurring condition in patients with ASD, could be a promising animal model which may advance our understanding of ASD.